Internecine strife in trade union organisations: status, competition and the effect of industry rationalisation and neo-liberalism. (4th March 2018) - Taylor, Greig
Abstract: Internal conflict in trade unions has been the subject of considerable academic interest. Often described as intra-union tensions, the basic divergence in priorities and concerns between union officialdom and their members on the shop floor has inspired a multiplicity of pioneering workplace studies and theoretical frameworks. However, while these hierarchical divisions in trade union organisations have received concerted attention, another manifestation of intra-union discord remains relatively under-explored. Inter-sectional or 'horizontal' conflict can be described as two sets of workers from different trade groups within the same union which are embroiled in competition or rivalry, usually in the same workplace. Although the loosely associated concept of sectionalism was identified as a re-emerging trend in British trade unionism in the 1960s and 1970s, there has been little attempt to document how conflict can occur between two sections of workers working side-by-side. This article will present a case of horizontal conflict from the British dock industry and consider under what circumstances and pressures the phenomenon is likely to occur. The two sections featured historically had an uneasy relationship and rationalisation of the industry, allied with the neoliberal restructuring of the British economy in the 1980s, exacerbated this. In these contexts, workers began to exhibit greater levels of group self-interest which amplified inter-sectional tensions further.